Rising Shallow Groundwater Level May Facilitate Seed Persistence in the Supratidal Wetlands of the Yellow River Delta - Feng, Lu; Peng, Ling; Cui, Qian; Yang, Hong-Jun; Ma, Jin-Zhao; Liu, Jing-Tao (Frontiers in Plant Science, 2022)
The saline groundwater level of many supratidal wetlands is rising, which is expected to continue into the future because of sea level rise by the changing climate. Plant persistence strategies are increasingly important in the face of changing climate. However, the response of seed persistence to increasing groundwater level and salinity conditions is poorly understood despite its importance for the continuous regeneration of plant populations. Here, we determined the initial seed germinability and viability of seven species from supratidal wetlands in the Yellow River Delta and then stored the seeds for 90 days. The storage treatments consisted of two factors: groundwater level (to maintain moist and saturated conditions) and groundwater salinity (0, 10, 20, and 30 g/L). After retrieval from experimental storage, seed persistence was assessed. We verified that the annuals showed greater seed persistence than the perennials in the supratidal wetlands. Overall, seed persistence was greater after storage in saturated conditions than moist conditions. Salinity positively affected seed persistence under moist conditions. Surprisingly, we also found that higher groundwater salinity was associated with faster germination speed after storage. These results indicate that, once dispersed into habitats with high groundwater levels and high groundwater salinity in supratidal wetlands, many species of seeds may not germinate but maintain viability for some amount of time to respond to climate change.